Mathematics
Sum1
2015-11-04 06:47:51
1. What is the value of x in the equation –6 + x = –3? (5 points) –9 –3 3 9 2. How many solutions does the equation –2a + 2a + 7 = 8 have? (5 points) One Two None Infinitely many 3. What is the value of y in the equation 2(2y – 16) = 0? (5 points) 4 6 8 9 4. How many solutions does the equation 5p – 4p – 8 = –2 + 3 have? (5 points) One Two None Infinitely many 5. The steps below show the incomplete solution to find the value of n for the equation 4n – 2n + 4 = –1 + 17: Step 1: 4n – 2n + 4 = –1 + 17 Step 2: 4n – 2n + 4 = 16 Step 3: 2n + 4 = 16 Which of these is most likely the next step? (5 points) 2n = 12 2n = 4 2n = 8 2n = 20 6. What is the value of z in the equation 2(4z – 3 – 1) = 166 – 46? (5 points) 14 15 16 17 7. What is the value of x in the equation –x = 3 – 4x + 6? (5 points) –9 –3 3 9 8. How many solutions does the equation 4n + 6 = 4 + 2 + 4n have? (5 points) Two Many None One 9. Which of these is a simplified form of the equation 6y + 4 = 8 + 2y + 2y? (5 points) 6y = 8 10y = 12 2y = 4 4y = 12 10. The work of a student to solve the equation 3(2x – 4) = 8 + 2x + 6 is shown below: Step 1: 3(2x – 4) = 8 + 2x + 6 Step 2: 5x – 7 = 14 + 2x Step 3: 5x – 2x = 14 + 7 Step 4: 3x = 21 Step 5: x = 7 In which step did the student first make an error and what is the correct step? (5 points) Step 2; 6x – 12 = 14 + 2x Step 2; 6x – 7 = 2(6 + x + 4) Step 3; 5x – 2x = 14 – 7 Step 3; 5x + 2x = 14 + 7 11. Which statement is true about the equation z – z + 1 = z + 1? (5 points) It has no solution. It has one solution. It has two solutions. It has infinitely many solutions. 12. What is the solution to the equation 3.6m – 2.7 = –1.8m? (5 points) m = 0.25 m = 0.5 m = 1.25 m = 1.5
ANSWERS
Maribel249204
2015-11-04 13:37:56

Question 1: –6 + x = –3 x = -3 + 6 x = 3 Hence, the answer is C. Question 2: –2a + 2a + 7 = 8  7 ≠ 8 Hence, the answer is C. Question 3: 2(2y – 16) = 0 4y - 32 = 0 4y = 0 + 32 4y = 32 y = [latex] frac{32}{4} [/latex] y = 8 Hence, the answer is C. Question 4: 5p – 4p – 8 = –2 + 3  p - 8 = 1 p = 1 + 8 p = 8 Hence, the answer is A. Question 5: 4n – 2n + 4 = –1 + 17 2n + 4 = 16 2n = 16 - 4 2n = 12 n = [latex] frac{12}{2} [/latex] n = 6 Hence, the answer is A. Question 6: 2(4z – 3 – 1) = 166 – 46 8z - 6 - 2 = 120 8z = 12 + 8 8z = 20 z = [latex] frac{20}{8} = frac{10}{4} = frac{5}{2} [/latex] z = 2.5 Hence, I think the question is wrong; it is missing a variable. Question 7: –x = 3 – 4x + 6 -x + 4x = 3 + 6 3x = 9 x = [latex] frac{9}{3} [/latex] x = 3 Hence, the answer is C. Question 8: 4n + 6 = 4 + 2 + 4n  4n - 4n + 6 = 6 6 = 6 Hence, the answer is C. Question 9: 6y + 4 = 8 + 2y + 2y 6y - 4y = 8 - 4 2y = 4 y = [latex] frac{4}{2} [/latex] y = 2 Hence, the answer is B. Question 10: 3(2x – 4) = 8 + 2x + 6 6x - 12 = 14 + 2x 6x - 2x = 14 + 12 4x = 26 x = [latex] frac{26}{4} = frac{13}{2} [/latex] x = 6.5 Hence, the answer is A. Question 11: z – z + 1 = z + 1 1 = z + 1 z = 1 - 1 z = 0 Hence, the answer is B. Question 12: 3.6m – 2.7 = –1.8m 3.6m + 1.8m = 2.7 5.4m = 2.7 m = [latex] frac{2.7}{5.4} = frac{1}{2} [/latex] m = 0.5 Hence, the answer is B.

ADD ANSWER